The Role of Field Experience Practice in Improving the Pedadogical Competency of PAI Students at Madrasah Aliyah Hasyimiyah - Hibrul Umam; Kartika Hidayati; Syafiul Amin; Siti Inayatul Umaroh (Penerbit Hellow Pustaka, 2026)
Field Practice (PPL) is an important part of the competency development process for prospective teachers, particularly the pedagogical competency of Islamic Religious Education (PAI) students. This study aims to analyze the role of PPL in improving the pedagogical competency of PAI students at Madrasah Aliyah Hasyimiyah. The research method used was descriptive qualitative, with data collection techniques through observation, interviews, and documentation. The data obtained were systematically analyzed to obtain a comprehensive overview of PPL implementation and its impact on students' pedagogical competency. The results indicate that PPL implementation plays a significant role in improving students' abilities in planning lessons, implementing effective learning processes, and conducting learning evaluations. Furthermore, PPL also helps students develop classroom management skills, understand student characteristics, and apply various learning methods. Therefore, it can be concluded that PPL makes a significant contribution to improving the pedagogical competency of PAI students as prospective professional educators